ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE SMA NEGERI 3 DEPOK DENGAN METODE USER CENTERED DESIGN (UCD) - Muhammad Fauzan Alhafizh, (2023)
SMA Negeri 3 Depok is one of the senior high schools in the city of Depok which has an information system that contains an information portal about the school's brief history, vision and mission, organizational structure, facilities and infrastructure, extracurricular information and student activities, alumni, and information on permanent teachers. and honorary. However, after conducting a survey with website managers and questionnaires to website users, it was found that the website did not yet have a user-friendly appearance, the website structure also did not have a good structure, this caused visitors to experience difficulties in choosing and finding the information they wanted. Therefore we need a method that can help improve the User Interface and User Experience of the Depok 3 Public High School Website, with this method it is hoped that it can help the process of developing and customizing websites according to school needs. The purpose of this study is to evaluate the User Experience and redesign the website user interface at SMA Negeri 3 Depok in order to reach a level of usability. The approach method used is User Centered Design (UCD) by carrying out questionnaires and prototyping with the System Usability Scale testing technique. After analyzing and testing the running website, the SUS test results yielded a score of 46 which is in the not acceptable category (Acceptability Scores). After the problem analysis and redesign process was carried out by applying the UCD approach and testing again using SUS, an increase in the final score of 76 was obtained which was included in the acceptable category on the website redesign prototype.